Case Series of Zone III Resuscitative Endovascular Balloon Occlusion of the Aorta in Traumatic Shock Patients - Byungchul Yu; Gil Jae Lee; Kang Kook Choi; Min A Lee; Jihun Gwak; Youngeun Park; Jung Nam Lee (Journal of Trauma and Injury)
Purpose There is increasing evidence in the literature regarding resuscitative endovascular balloon occlusion of the aorta (REBOA) globally, but few cases have been reported in Korea. We aimed to describe our experience of successful Zone III REBOA and to discuss its algorithm, techniques, and related complications. Methods We reviewed consecutive cases who survived from hypovolemic shock after Zone III REBOA placement for 4 years. We reviewed patients’ baseline characteristics, physiological status, procedural data, and outcomes. Results REBOA was performed in 44 patients during the study period, including 10 patients (22.7%) who underwent Zone III REBOA, of whom seven (70%) survived. Only one patient was injured by a penetrating mechanism and survived after cardiopulmonary resuscitation. All patients underwent interventions to stop bleeding immediately after REBOA placement. Conclusions This case series suggests that Zone III REBOA is a safe and feasible procedure that could be applied to traumatic shock patients with normal FAST findings who receive a chest X-ray examination at the initial resuscitation.